Apical Leakage of Bioceramic versus Epoxy Resin–Based Sealers in Single-Cone Obturation: A Systematic Review and Meta-Analysis - Vikri Sandya Dhika; Veriantara Satya Dhika (Fakultas Kedokteran Universitas Pelita Harapan, 2026)
Background: Bioceramic sealers paired with the single-cone obturation technique represent an evolving clinical paradigm, yet no systematic review has exclusively evaluated their apical sealing performance against epoxy resin–based sealers within this specific technique. This study aimed to systematically compare the in vitro apical leakage of bioceramic versus epoxy resin–based sealers used with single-cone obturation in extracted human teeth. Methods: A systematic search of PubMed, Embase, and Scopus was conducted from inception to 1 April 2026, following PRISMA 2020 guidelines. Only English-language publications were included. In vitro and ex vivo studies comparing apical leakage between bioceramic and epoxy resin sealers with at least one single-cone obturation group were included. Risk of bias was assessed using the QUIN tool. Standardized mean differences were pooled using a random-effects model for studies reporting comparable continuous leakage data. Result: Eight studies met the inclusion criteria. Five were rated as low risk of bias and three as medium risk. Meta-analysis of four studies with continuous leakage data (n = 77 per group) yielded a pooled SMD of −1.75 (95% CI: −3.92 to 0.42), favoring bioceramic sealers, though heterogeneity was considerable (I² = 88.1%). Narrative synthesis of the remaining four studies showed directionally consistent trends supporting bioceramic sealers across bacterial leakage and nanoleakage methodologies. Conclusions: Bioceramic sealers demonstrated a trend toward less apical leakage than epoxy resin–based sealers with single-cone obturation; however, evidence certainty remains low due to high heterogeneity and limited study numbers. Standardized multicenter in vitro studies and long-term clinical trials are warranted.